Pemanfaatan Air Cucian Beras sebagai Pupuk Organik Cair dan Pengaruhnya terhadap Kesuburan Tanah: Tinjauan Literatur - Priska Rahmat Yanti Zega (CV. SINAR HOWUHOWU, 2026)
This research discusses the potential of rice wash water as an environmentally friendly liquid organic fertilizer (POC). Rice rinsing water contains carbohydrates, vitamin B complex, and important minerals such as potassium, phosphorus, and magnesium, which are beneficial for plant growth. Several studies have shown that its use can increase the growth of plant height, number of leaves and stem diameter. In addition, rice rinse water contains decomposing microorganisms that accelerate the decomposition of organic matter and improve soil quality. The use of rice rinse water also helps reduce household waste and dependence on chemical fertilizers. With its complete nutritional content and easy availability, rice wash water has great potential to support sustainable agriculture.